Flow Akademik Ditinjau dari Persepsi Kompetensi Akademik dan Dukungan Guru pada Siswa SMA - Devi Hastiana; Nurul Hidayah (Empathy : Jurnal Fakultas Psikologi, 2021)
Academic Flow in Terms of Perceived Academic Competence and Teacher Support for High School StudentsÂ Academic flow has a very important role in the field of education to increase academic success. This study aims to examine the relationship between perceived academic competence and teacher social support with academic flow. The subjects of this study were all 92 students of SMA "X" in Musi Banyuasin district. The research method used is quantitative, data collection tools in the form of a psychological scale and data analysis using multiple regression analysis techniques with the help of the IBM SPSS for windows 21.0 computer program. The analysis results show a correlation coefficient (r) of 0.292 and a significance level (p) of 0.005 (p< 0.01) so it can be concluded that there is a very significant positive relationship between perceived academic competence and teacher support with academic flow. The higher the perceived academic competence felt by students, the higher the academic flow. The higher the teacher support received, the higher the academic flow and conversely the lower the perception of competence felt by students, the lower the academic flow as well as teacher support, the lower the teacher support received by students, the lower the academic flow. The effective contribution given by each variable to the academic flow is from the perceived academic competence by 62%, while from teacher support it is 12.3% and the remaining 25.7% is influenced by other factors.